The Modelling of The Effect of Air Fuel Ratio on Unburned Hydrocarbons for MILD Combustion - M. M., Noor; Wandel, Andrew P.; Yusaf, Talal (2012)
Unburned hydrocarbons (UHC) are a waste and pollution to the environment. UHC will happen when rich combustion occurred. In the case of exhaust gas recirculation (EGR) utilized to diluted the oxidiser, UHC in the EGR can result in unwanted combustion at unwanted locations (i.e. in the EGR pipe). FLUENT was utilised to model the open furnace. The volume flow rate for air and fuel was the main parameter of the study. In order to consume all the fuel by the combustion, the air fuel ratio (AFR) must be higher than 5:1. Lean combustion (AFR more than 5:1) will eliminate the possibility of UHC in flue gas.